2011
DOI: 10.1016/j.bpj.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Pathway Model of the Biological Catch-Bond as a Limit of the Allosteric Model

Abstract: Catch-binding is a counterintuitive phenomenon in which the lifetime of a receptor/ligand bond increases when a force is applied to break the bond. Several mechanisms have been proposed to rationalize catch-binding. In the two-pathway model, the force drives the system away from its native dissociation pathway into an alternative pathway involving a higher energy barrier. Here, we analyze an allosteric model suggesting that a force applied to the complex alters the distribution of receptor conformations, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…They are dubbed catch bonds and are thought to characterize TCR interactions involving pMHC agonists (56). Note that despite a number of studies, the structural mechanisms that underlie catch bond behavior, including those postulated for the TCR, remain poorly understood (57)(58)(59). Second, bond formation is a multistep process leading to a progressive increase in bond stability.…”
Section: Tcr Mechanosensing As the Initiating Eventmentioning
confidence: 98%
“…They are dubbed catch bonds and are thought to characterize TCR interactions involving pMHC agonists (56). Note that despite a number of studies, the structural mechanisms that underlie catch bond behavior, including those postulated for the TCR, remain poorly understood (57)(58)(59). Second, bond formation is a multistep process leading to a progressive increase in bond stability.…”
Section: Tcr Mechanosensing As the Initiating Eventmentioning
confidence: 98%
“…Correspondingly, a one state two path approach is not applicable to our experimental data as it diverges in the low force regime. More elaborate approaches have been reported that take account of force-induced deformations (29), protein water interfaces (50), fluctuating energy barriers (26), or two bound states separated by an energy barrier (22,23,28,(31)(32)(33)48).…”
Section: Single Molecule Force Clamp Experimentsconstant Force Experimentioning
confidence: 99%
“…Namely, catch bond behavior could be found in PSel-PSGL-1 (4), FimH-mannose (18), actomyosin (19), platelet glycoprotein Iba-von Willebrand factor (20), and integrins (21) thus verifying the general concept of this most exciting and paradox discovery in cell adhesion. Beyond its experimental findings a couple of theoretical models were formulated helping to rationalize this counterintuitive phenomenon (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…83 This type of surface is relevant for modeling the so-called catch bonds. [84][85][86][87][88][89][90][91][92][93][94][95][96][97]…”
Section: Potential Energy Surface With An Elementary Pathwaymentioning
confidence: 99%